SAT0442 EVOLVEMENT OF SWOLLEN JOINTS IN THE FIRST YEAR OF EARLY PSORIATIC OLIGOARTHRITIS. (2nd June 2020) - Vis, M.; Marc, K.; Tchetverikov, I.; Hazes, J.; Luime, J.
Abstract : Background: Oligoarthritis and polyarthritis are the predominant phenotypes in PsA. Previous we have shown that patients with oligoarthritis suffer a similar loss in quality of life as polyarthritis patients. 1 Although oligoarthritis is one of the most prevalent form, ample data is available on this phenotype. 2-5 Objectives: To evaluate the evolution of swollen joint count over the first year since diagnosis and to assess baseline difference in those groups that evolved differently over time. Methods: Our study is embedded in the Dutch south-west Early Psoriatic Arthritis (DEPAR) prospective cohort study. We described patient characteristics using simple descriptive analysis techniques. For the comparison across groups univariable multinomial logistic regression was used in STATA15. Oligoarticular disease was defined as 2, 3 or 4 swollen joints, Results: 175 patients had a complete 12-month evaluation as of February 2019 (80% of all included patients with oligoarthritis). Baseline characteristics are shown in table 1 . In total 63 percent of the patients (111/175) had resolution of swollen joints at 1 year. (figure 1 ). Over the first year, 27 patients had consistently no swollen joints since their 3 month evaluation, 26 had no swollen joint from 6 months and 12 from 9 months and 11 at 12 months. 65 of the 175 (37%) had inconsistently no swollen joints (intermittent) during the first year. In 8% of the patients values were missing to determine to which group they belonged. Univariable multinomial logistic regression of baseline characteristics showed that the group that had resolution of swollen joints 'early' (within 6 months) compared to (i) the group that 'never' had resolution differed in having fewer tender joints; (ii) the group having 'late' resolution of swollen joints (after 6 months) showed little difference and;(iii) the 'intermittent' group varied in smoking status, fatigue, being female and age. Multivariable analysis may reveal other patterns, but requires a larger sample than that currently available. Conclusion: In our set of real world data, about one third of the PsA patients with oligoarticular disease had no resolution of swollen joints at 1 year. About half of these patient had consistently inflamed joints over time. Another third of the PsA patients had intermittently inflamed joints. At baseline these groups seems comparable in clinical presentation, demographics and PROMs, although some variation existed between early versus never and early versus intermittent resolution of swollen joints. Both indices provide room for improvement in the management of oligoarticular disease in PsA. References: [1]Wervers K et al. 2018 Nov;45(11):1526-1531 [2]Jones SM, et al. Br J Rheumatol. 1994;33(9):834-9 [3]Dönmez S, et al Clin Rheumatol. 2015;34(6):1091-6 [4]Iannone F, et al Scand J Rheumatol. 2015;44(3):192-9 [5]Kruithof E, et al Arthritis Res Ther. 2005;7(3):R569-80 Disclosure of Interests: Marijn Vis Grant/research support from: Novartis, Pfizer – grant/research support, Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Novartis, Pfizer – consultant, Kok Marc Grant/research support from: Novartis, Pfizer, Celgene, Lilly, UCB, Consultant of: Novartis, Celgene, Speakers bureau: Celgene, Ilja Tchetverikov: None declared, Johanna Hazes: None declared, Jolanda Luime: None declared